Climate change and the Kenyan dairy industry - Cramer, Laura K. (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
A regional knowledge management workshop for the dairy sector was held on the 14th January 2025 by the Eastern Africa Farmers Federation (EAFF) in Naivasha, Kenya. The session brought together stakeholders to exchange experiences, strengthen farmer organisation networks, and discuss policy priorities. This presentation, delivered by Dr Laura Cramer, begins with an overview of climate change impacts and implications for the dairy industry in East Africa, highlighting adaptation options (e.g. cooling techniques, resilient breeds and water and feed storage techniques) to build resilience. It then focuses on greenhouse gas emissions mitigation in Kenyan dairy systems, outlining key interventions (e.g. improved feeding, reducing milk loss and waste, biogas digesters, energy efficiency) and emphasising the critical role of animal health in reducing emissions.